New approaches to screening and management of neonatal hypoglycemia based on improved understanding of the molecular mechanism of hypoglycemia - Stanley, Charles A.; Thornton, Paul S.; De Leon, Diva D. (Frontiers in Pediatrics, 2023)
For the past 70 years, controversy about hypoglycemia in newborn infants has focused on a numerical “definition of neonatal hypoglycemia”, without regard to its mechanism. This ignores the purpose of screening newborns for hypoglycemia, which is to identify those with pathological forms of hypoglycemia and to prevent hypoglycemic brain injury. Recent clinical and basic research indicates that the three major forms of neonatal hypoglycemia are caused by hyperinsulinism (recognizing also that other rare hormonal or metabolic conditions may also present during this time frame). These include transitional hypoglycemia, which affects all normal newborns in the first few days after birth; perinatal stress-induced hypoglycemia in high-risk newborns, which afflicts ∼1 in 1,200 newborns; and genetic forms of congenital hyperinsulinism which afflict ∼1 in 10,000–40,000 newborns. (1) Transitional hyperinsulinism in normal newborns reflects persistence of the low glucose threshold for insulin secretion during fetal life into the first few postnatal days. Recent data indicate that the underlying mechanism is decreased trafficking of ATP-sensitive potassium channels to the beta-cell plasma membrane, likely a result of the hypoxemic state of fetal life. (2) Perinatal stress-induced hyperinsulinism in high-risk infants appears to reflect an exaggeration of this normal low fetal glucose threshold for insulin release due to more severe and prolonged exposure to perinatal hypoxemia. (3) Genetic hyperinsulinism, in contrast, reflects permanent genetic defects in various steps controlling beta-cell insulin release, such as inactivating mutations of the KATP-channel genes. The purpose of this report is to review our current knowledge of these three major forms of neonatal hyperinsulinism as a foundation for the diagnosis and management of hypoglycemia in newborn infants. This includes selection of appropriate interventions based on underlying disease mechanism; combined monitoring of both plasma glucose and ketone levels to improve screening for infants with persistent forms of hypoglycemia; and ultimately to ensure that infants at risk of persistent hyperinsulinemic hypoglycemia are recognized prior to discharge from the nursery.